Influence of SMS (Short Message Service) Language on Academic Writing of Post-Graduate Students - Nasir Mahmood, Sidra Tahir, Sumbal Asghar (JSSH, 2023)
If you cannot understand the above sentences, then you most likely have not been exposed to the newly born language of the 21st century and it is not your fault because this new century has brought a remarkable technological revolution in the means of communication that has introduced the world with a new term “global village”.